2014
DOI: 10.1186/1752-1947-8-331
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis manifesting as a colon polyp: a case report

Abstract: IntroductionSchistosomiasis is a rare disease with a common intestinal involvement. However, colon polyps associated with Schistosoma in the absence of inflammation have rarely been reported, especially in young people; this is the first case with the following presentation.Case presentationWe describe the case of a 20-year-old Ethiopian woman living in Lebanon who presented with nonspecific abdominal symptoms. Her biochemical profile was normal in addition to the results of her stool and urine tests. A colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…One complication observed in patients is the occurrence of colon polyps that are shed and cause intestinal bleeding ( 160 ). Probably this may happen when unsuccessful trapped eggs become calcified, losing their fibrinolytic potential and leading to chronic granulomas as seen in the liver.…”
Section: Mechanism Of “Eggs-cretion”mentioning
confidence: 99%
“…One complication observed in patients is the occurrence of colon polyps that are shed and cause intestinal bleeding ( 160 ). Probably this may happen when unsuccessful trapped eggs become calcified, losing their fibrinolytic potential and leading to chronic granulomas as seen in the liver.…”
Section: Mechanism Of “Eggs-cretion”mentioning
confidence: 99%
“…In our case, the identification of colonic polyp consisting of schistosoma eggs, absence of other intra-abdominal pathology, and the improvement of her symptoms with anti-schistosomiasis treatment strongly imply the diagnosis of intestinal schistosomiasis. We believe that our case is probably the only patient with intestinal schistosomiasis presenting with abdominal pain and polyps that has ever been reported in U.S. [10]. As shown in our patient and literature, clinical symptoms and laboratory tests are typically not specific enough to aid the diagnosis of intestinal schistosomiasis, therefore, careful history acquisition and egg identification are crucial to establish early diagnosis and prevent complications.…”
Section: Discussionmentioning
confidence: 66%
“…Atik et al reported an extremely rare presentation in a 25‐year‐old Brazilian patient who presented colonic perforation and fecal peritonitis due to multiple colonic bilharzial polyps, and thick colonic wall perforating into the abdominal cavity was detected in postlaparotomy histopathology. In addition, Issa et al reported large right‐side colonic bilharzial polyp is a 20‐year‐old Ethiopian woman, who presented with long‐standing abdominal pain. Our patient did not report any symptoms suggestive of bilharziasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although any part of the bowel may be the seat for bilharzial polyps, it is commonly encountered in the rectosigmoid region. However, large polyps were also reported in the ascending colon and the cecum …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation